Pengaruh Kesegaran Tebu (Saccharum officinarum L.) pada Kualitas Gula Cetak Merah - Harjanti, Ratna Sri; Hamami, Rahmi Sabrina; Kusumawati, Anna; Rizal, Azhari; Mustangin, Muhammad; Suryaningrum, Dwi Aryani; Yunaidi, Yunaidi (Politeknik Negeri Lampung, 2024)
To maintain sugarcane freshness, it is crucial to process it promptly after harvest. This study aims to analyze the quality of molded brown sugar derived from raw materials with varying levels of freshness. The research adopts a non-factorial design involving three main treatments: the duration of stay on the first, second, and third days, with three replications. Parameters observed during the molded brown sugar production process include brix, pol, purity, and reducing sugar from raw juice; brix, pol, purity, and reducing sugar from clear juice; color, brix, moisture content, and reducing sugar of sugar. Data analysis is performed using analysis of variance (ANOVA) with the application of Duncan's multiple range test. The purity value in raw juice data H1 with a value of 89.54 significantly differs from data H3 with a value of 73.83. Similarly, reducing sugar in raw juice H1 at 0.74 significantly differs from H3 at 0.93. The purity value in clear juice H1 at 88.34 significantly differs from H3 at 75.40. As for reducing sugar in clear juice, H1 at 0.81 is significantly smaller than H3 at 1.18. Regarding the difference between open-pan and close-pan cooking treatments, it is concluded that the cooking system producing the best molded brown sugar is the close-pan system, evident in both color results and the reduced sugar content of molded brown sugar. The best color for molded brown sugar is found in treatment H1 (day 1) with the close-pan system at 551.40. The lowest reducing sugar content is observed in treatment H1 (day 1) with the close-pan system at 0.94.